(untitled) (World Economics and Finance Bulletin, 2023)
The article presents study of issues related to the phenomenon of transport corridors. The topic, which has received sufficient reflection in the academic literature, still remains in demand, which is associated with the dynamism of the object of study itself. A poorly developed aspect of the problem is the geopolitical component of the processes of formation, formation and development of transport corridors. This article aims to fill this gap. In the presented work, the goal was to study the influence of geopolitical factors on the development of transport corridors, changes in their structure. As part of this goal, research was carried out in the following areas: the study of the nature of geopolitical factors, political motives for the creation, management and control of transport corridors. As a result, the author substantiates a qualitatively new level of complexity of the global geopolitical landscape, which determines the development of transport corridors. The article explores the processes of formation of two dialectically opposite trends: the "compression" of space due to an increase in the intensity and speed of communication and its "expansion" due to the integration of new territories into the global transport system. The article complements the content, which is aggregated around the urgent need for the formation of a new scientific discipline "geopolitics of transport".